(untitled) (Web of Teachers: Inderscience Research, 2026)
In contemporary second language education, cognitive and affective variables have been increasingly recognized as crucial determinants of academic success. This study examines the predictive roles of critical thinking and mindfulness in academic achievement among Iranian learners of English as a Foreign Language (EFL). Adopting a quantitative correlational design, data were collected from 120 university-level EFL learners in Iran using standardized measures of critical thinking and mindfulness, alongside official academic records. Pearson correlation and multiple regression analyses revealed significant positive relationships among critical thinking, mindfulness, and academic achievement. The findings indicate that critical thinking and mindfulness jointly account for a substantial proportion of variance in learners’ academic performance, with critical thinking emerging as the stronger predictor. The study underscores the importance of integrating higher-order thinking skills and mindfulness-oriented practices into EFL pedagogy.